Highly stretchable silicone rubber nanocomposites incorporated with oleic acid‐modified Fe3O4 nanoparticles. Issue 2 (11th August 2021) - Zeng, Yu; Zhou, Neng; Xiong, Chenhan; Huang, Zhiyong; Du, Guoping; Fan, Zhaoyang; Chen, Nan
Abstract: Silicone rubber composites have attracted wide attention due to their excellent thermal stability and climate resistance. However, it is still a challenge to synthesize these composites with high tensile property without external stimulation. Meanwhile, incorporation of superparamagnetic iron oxide nanoparticles to fabricate magnetic nanocomposites have a broad application prospect. In the present work, aiming to improve the mechanical and magnetic properties of the silicone rubber composite, fumed silica and different content of oleic acid‐modified Fe3 O4 nanoparticles are well dispersed in the silicone rubber matrix. The synthesized nanocomposites exhibit excellent thermal stability, superelasticity, superparamagnetic property, and sensitive magnetic response. In particular, a high elongation at break of 1931%, a low storage modulus of 0.56 MPa and a deflection of 27 mm under an applied magnetic field of 1.31 Oe are obtained in the silicone rubber nanocomposite. The present work provides a feasible way to prepare silicone rubber matrix nanocomposites with excellent mechanical and magnetic performance. Abstract : Aiming to improve the mechanical and magnetic properties of the silicone rubber composite, fumed silica and different content of oleic acid‐modified Fe3 O4 nanoparticles are well dispersed in the silicone rubber matrix. The synthesized nanocomposites exhibit excellent thermal stability, superparamagnetic property, sensitive magnetic response and superelasticity with a high elongation at break of 1931%. This provides a feasible way to prepare silicone rubber matrix nanocomposites with excellent mechanical and magnetic performance.